Handbook of Herbs and Spices 2012
DOI: 10.1533/9780857095688.417
|View full text |Cite
|
Sign up to set email alerts
|

Oregano

Abstract: The present review focuses on the various Oregano species, oregano being one of the most famous -and economically important -culinary herbs in the world. The botany and chemotaxonomy of the species is thoroughly reported, along with cultivation methods and breeding techniques (including biotechnology), details of the chemical constituents of its essential oil, its traditional uses and medicinal uses (including its applications as an antimicrobial and antioxidant). Quality specifi cations and commercial issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…The treatment with oregano (T2) evinced countable yeast and mold count from sixth day. This might be due to the high phenolic content of oregano that prevents sporulation of yeasts by arresting cellular energy (Kintzios, ). Studies by Schmitz, Weidenboerner, and Kunz () have shown that 2% of ground oregano inhibits the growth of Alternaria , Fusarium , Penicillium, and Aspergillu s. By the end of the storage, all samples revealed pronounced ( p < .05) Y & M growth, however, comparatively slower growth rate were observed in treatments than control pertaining to higher phenolic content of herbs.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The treatment with oregano (T2) evinced countable yeast and mold count from sixth day. This might be due to the high phenolic content of oregano that prevents sporulation of yeasts by arresting cellular energy (Kintzios, ). Studies by Schmitz, Weidenboerner, and Kunz () have shown that 2% of ground oregano inhibits the growth of Alternaria , Fusarium , Penicillium, and Aspergillu s. By the end of the storage, all samples revealed pronounced ( p < .05) Y & M growth, however, comparatively slower growth rate were observed in treatments than control pertaining to higher phenolic content of herbs.…”
Section: Resultsmentioning
confidence: 84%
“…The treatment with oregano (T2) evinced countable yeast and mold count from sixth day. This might be due to the high phenolic content of oregano that prevents sporulation of yeasts by arresting cellular energy (Kintzios, 2012). Studies by Schmitz, Weidenboerner, and Kunz (1993) have shown that 2% of ground oregano inhibits the growth of Alternaria, Fusarium, Penicillium, and Aspergillus.…”
Section: Microbiological Characteristics Of Meat Breadmentioning
confidence: 99%
“…All these studies indicate that any differences between studies can be a result of the different chemical composition of the EOs examined and concentration used. Chemical polymorphism of EOs is characteristic to species of Thymus and Oregano (Kintzios, 2012;Ložienė & Venskutonis, 2005). It is well known that environmental factors such as temperature, moisture, the chemical composition of the soil, stage of vegetative cycle, and harvesting seasons influence the chemical composition of EOs (El-Zaeddi, Martínez-Tomé, Calín-Sánchez, Burló, & Carbonell-Barrachina, 2016;Ložienė & Venskutonis, 2005).…”
Section: Food Chemistrymentioning
confidence: 99%
“…Oregano, belonging to the Lamiaceae family (Kintzios ), is one of the most commonly consumed herbs in Europe (CBI ). The herb grows naturally in the Mediterranean region, Turkey being a main producer, and is used as an important flavor ingredient in food dishes such as pizza, sausages, meat, dressings, and soups (Kintzios ).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic aroma of oregano is highly dependent on its volatile oil content and composition. Due to its aroma, antioxidant, and other health‐related properties, the volatile oil of oregano is of great commercial importance (CBI ; Kintzios ). If special care is not taken during thermal decontamination processes, the sensory properties and quality of herbs and spices can be severely affected.…”
Section: Introductionmentioning
confidence: 99%